2017
DOI: 10.1007/s11746-017-3031-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Camelina sativa Protein Isolates and Mucilage

Abstract: Processes for the production of protein isolates from camerlina Camelina sativa were developed by modifying the procedure used for other seeds from the Brassicaceae family, such as rapeseed and mustard. The procedure consisted of defatting the seed followed by alkaline extraction at pH 11, ultra‐ and diafiltration using a 5‐kDa membrane, isolelectric precipitation of the proteins at pH 5 and recovery of the acid soluble protein isolates (SPI) after further filtration and drying. Protein yields as precipitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…Protein yields were low at 11.4% for the soluble proteins and 10.7% for the precipitated proteins, while the protein contents were 67% and 42%, respectively. Precipitated protein yield reported by Boyle et al [11] was almost four times higher than the one reported by Sarv et al [66] One possible explanation is the higher alkaline pH that was used for the extraction and the addition of ammonium sulfate (pH 12 for Boyle et al [11] vs pH 11 for Sarv et al [66] ). Li et al [65] studied the impact of the pH on the solubilization of glutelin, the main protein present in camelina meal, and they found that the solubility of glutelin was ≈1.75 times higher at pH 12 than at pH 11.…”
Section: Camelina Protein Composition and Extractionmentioning
confidence: 70%
See 4 more Smart Citations
“…Protein yields were low at 11.4% for the soluble proteins and 10.7% for the precipitated proteins, while the protein contents were 67% and 42%, respectively. Precipitated protein yield reported by Boyle et al [11] was almost four times higher than the one reported by Sarv et al [66] One possible explanation is the higher alkaline pH that was used for the extraction and the addition of ammonium sulfate (pH 12 for Boyle et al [11] vs pH 11 for Sarv et al [66] ). Li et al [65] studied the impact of the pH on the solubilization of glutelin, the main protein present in camelina meal, and they found that the solubility of glutelin was ≈1.75 times higher at pH 12 than at pH 11.…”
Section: Camelina Protein Composition and Extractionmentioning
confidence: 70%
“…For the spring cultivars (66), the total concentration of flavonoids varied from 404 ± 38.5 to 429.9 ± 13.8 mg kg −1 , which was significantly lower than for the winter cultivars (9) (507.3 ± 51.4 to 526.4 ± 10.4 mg kg −1 ). Similar results were reported for the phenolic acids, with the concentration ranging from 2043.6 ± 62.5 to 2174.0 ± 145.2 mg kg −1 in the spring cultivars and from 3936.0 ± 210.8 to 3704.7 ± 195.4 mg kg −1 in the winter cultivars.…”
Section: Oilseedmentioning
confidence: 73%
See 3 more Smart Citations